Faktor Kemampuan Non Keuangan: Berpengaruh Pada Model Pengembangan Pada Industri Batik (Studi pada Kampung Batik Laweyan) - Vidiyanna Rizal Putri; Meta Andriani; Liana Mangifera (Politeknik Caltex Riau, 2019)
This research is aims to identify the characteristics of internal environment as well as the profile of the management capability of the batik industry in Kampung Laweyan, Surakarta. Furthermore, to know the factors of the ability of management is to encourage the main factors in managing business for batik industry. The object of this research is batik industry in Kampung Laweyan in ​Kecamatan Laweyan, Surakarta. The study involved 100 batik entrepreneurs with 65 samples middle and small-scale batik entrepreneurs in Laweyan, where the overall input of the questionnaire was good. The analysis used is descriptive analysis and quantitative analysis by using multiple linier regression analysis and multilevel regression analysis (Moderate Regression Analysis). The result of this research shows that from 5 independent variables and dependent variables only 3 hypothesis are accepted, they are operational management capabilities which have a negative effect, marketing management and human resources management’s ability have positively influence to nonfinancial performance. Keyword: business development model, non-financial performance, batik industry